A study on the employees acceptance towards islamic banking products: A case of Perbadanan Kemajuan Iktisad Negeri Kelantan (PKINK) / Muhammad Afizie Abdullah and Nur Afifah Zakaria - Abdullah, Muhammad Afizie; Zakaria, Nur Afifah (2014)
This study begins with the brief history of Islamic Banking at early age in Malaysia. Then this study is followed by a discussion on a survey undertaken to know the employees acceptance towards Islamic Banking products in Perbadanan Kemajuan Iktisad Negeri Kelantan (PKINK). A set of questionnaires was distributed to the respondent which is the employees at PKINK randomly. Several factors such as Knowledge, Religion Beliefs and Philosophy of Islamic Banking that being discussed in this research are to know their acceptance towards Islamic Banking products. The data is analysed using Descriptive Analysis, Reliability, Correlation and Regression Analysis by using Statistical Package for Social Science (SPSS). Besides that, Regression Analysis was used to test the hypotheses in this study. In this study, the result shows that Knowledge and Philosophy of Islamic Banking have significant influence with the employees acceptance in PKINK, whereas for Religion Beliefs, the result shows that it is not significant. Besides, for this study, the most significant influence is Philosophy of Islamic Banking. The results of this study can facilitate the people especially the management, Islamic banker and employees give the best action in order to cover some flaws in Islamic banking aspects